Pendampingan Pembuatan Media Pembelajaran Menggunakan Canva Kepada Para Guru SMP - Jelimun, Maria Olga; Selamat, Ely Heldydiana; Anung, Matilda Saputri; Jumat, Helena Indriyani; Darma, Benedicto Cahya (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
. The fundamental problems in this Community Service activity are (1) the teacher's ability to utilize technology as a learning medium. (2) Teachers tend not to use technology in designing learning media. The method used in implementing PKM is the empowerment model. This activity aims to assist the teachers to design interactive technology based learning media. This model is implemented using the following steps: 1) Observations are carried out to obtain joint agreement regarding the mechanism for mentoring activities. 2) holding a workshop which aims to explain and provide general knowledge regarding learning media and the Canva application. 3) The pretest is carried out to obtain comparative scores before mentoring and after mentoring. 4) Assistance in creating learning media using Canva. 4) The post test was carried out to see the teacher's skills and achievements in creating learning media using Canva. The scores obtained in the two tests created were analyzed statistically using the JAPS application. The scores between the two tests are different from each other. The median value of the pre-test results received a score of 55.0 which is categorized as "Low". Meanwhile, the median value from the post-test results received a score of 80.0 and was categorized as "Good". From these results, it can be concluded that the highest median value was obtained by the post-test value. Apart from that, the mean score obtained by students also varies based on each test given. From the pre-test score obtained by students received a score of 55.33 which is categorized as a "Low" score. Meanwhile, the post-test score obtained was 77.77 which was categorized as "Good". From these results, it can be concluded that the mean post-test score was higher than the pre-test score. It means that the teachers are able to use Canva in designing their learning media.